Electrostatic stratification of the global cloud system by the self-consistent field of the metastable electronion subsystem of the atmosphere - T.A. Belyi; Yu.V. Zelenin (Геофизический журнал, 2013)
Analysis of frequency distribution of the heights of clouds formation has been conducted by the data of airplane sounding for compatibility to the structure of surface and highaltitude electrostatic field. Coincidence of maximal sites of frequency distribution of cloud heights with zero values of distribution of threedimensional charges of atmosphere has been found. Correspondence does not depend on the type of cloudiness, though cloud distributions by themselves differ essentially for the different types. It has been shown that frequency distribution of the heights of clouds formation is related to gravity polarization of the active atmospheric medium — metastable undercooled coulomb plasma of thermalizing atmospheric electrons. Effective dielectric permeability of such a medium varies within the limits of 104—106 CGSE. Approximate solution of self consistent Poisson equation for medium field of atmospheric electrons corresponding to Landau equation for the firstorder phase transitions has been given. Exact solution has been found for the equation depending on boundary conditions. Parameters of solution, module of elliptic function and effective length of screening have been chosen in accordance with the experiment and reproduce altitude run of potential correctly. Module dependence has a critical character of firstorder phase transitions. The nature of dependence is related to heavy mode of lengmure vibrations of ionicelectronic atmosphere subsystem.